Properties And Decay Resistance Of Mahang (Macaranga Sp.) Treated With Phenolic Resin And Acrylic Monomer Using Vacuum-Pressure Process - Ang, Aik Fei (2010)

(untitled)
Mahang (Macaranga sp.) was treated with phenolic resin and methyl methacrylate (MMA) monomer. Impreg is a type resin treated wood while Compreg refers to resin treated compressed wood. Mahang wood was impregnated with 15, 20 and 25% (Impreg) and 15% (Compreg) phenolic resin using vacuum-pressure process. The vacuum-pressure process could maximize the penetration of resin and monomer into wood. The resin in Impreg mahang was partially cured at 65ºC for 24 h prior to fully cure at 150ºC for 30 min in an oven while Compreg mahang was fabricated by compressed the treated wood with 0.3, 0.4 and 0.5 compression ratios (CR). The resin in treated wood was partially cured at 65ºC for 56 h prior to fully cure at 150ºC for 30 min under hot press. For MMA-treated wood, polymerization was carried out in a combination with a crosslinker trimethylolpropane trimethacrylate (TMPTMA). Polymerization was carried out by catalyst heat treatment at 65 ºC for 2 h. The resin weight percent gain (WPG) for Impreg mahang was in the range of 33-51% whereas for Compreg mahang was 27-31%. For MMA-treated wood, a fairly consistent acrylic retention ranged from 187.5-229.6% was found in the wood when treated with or without crosslinker. The resin WPG of Impreg mahang was increased significantly when the levels of phenolic resin increased from 15-25%. The resin WPG for Compreg mahang was not differed significantly among 0.3, 0.4 and 0.5 CRs. It was found that the concentrations of crosslinker gave significant effect on the polymerization of MMA. The polymerization is at maximum with 1% crosslinker and beyond this concentration the polymerisation decreased. The density of Impreg, Compreg and MMA-treated mahang was improved significantly from 31-53%, 89-139% and 188-216%, respectively compared to untreated wood. The Impreg and MMA-treated mahang showed improvement in the dimensional stability compared to untreated wood but there is no improvement was recorded for Compreg mahang. The phenolic resin concentrations did not gave significant effect in the ASE of Impreg and Compreg mahang while the crosslinker concentrations gave significant effect in the ASE of MMA-treated mahang. Mositure excluding efficiency (MEE) of Impreg, Compreg and MMA-treated mahang was also improved significantly from 6.27-9.63%, 15.48- 27.85% and 40.93-55.68%, respectively compared to untreated wood. The phenolic resin and crosslinker concentrations did not gave significant effect in the MEE. The improvement in reduction in water absorption (R) of Impreg, Compreg and MMA-treated mahang against untreated wood was ranged from 49.02-65.04%, 67.54-71.63% and 91.18-93.22%, respectively. The phenolic resin and crosslinker concentrations did not gave significant effect in the (R) except for Impreg mahang. Mechanical strength of Impreg mahang in terms of compressive stress and hardness were improved 75 to 266% and 32 to 62%, respectively compared to untreated wood. The compressive stress and hardness of MMA-treated mahang were 577 to 1387% and 219 to 386% greater than untreated wood. However, the stiffness (modulus of elasticity) did not change.All the mechanical properties for Compreg mahang were improved significantly compared to untreated wood. In terms of specific strength (strength to density ratio), the treated material has less stiffness and less strength in lateral direction compared to untreated wood. However, the specific compressive strength perpendicular to the grain and hardness of the treated material were superior compared with the untreated. The decay resistance of Impreg, Compreg and MMA-treated mahang against white rot fungus, Pycnoporus sanguineus was improved significantly compared to untreated wood.